2010
DOI: 10.1007/s11434-009-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of 3D scaffold using 3D plotting system

Abstract: In this paper, we design and fabricate a 3D scaffold using rapid prototyping (RP) technology for tissue engineering. The scaffold should have a three-dimensional interconnected pore network. We fabricate a polycaprolactone (PCL) scaffold with interconnecting pores and uniform porosity for cell ingrowth using a 3D plotting system. In order to keep the three dimensional shape under mechanical loading while implanted, we design an oscillating nozzle system to increase elastic modulus and yield strength of PCL str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This study investigated the structural properties of hydroxyapatite scaffold for bone substitute replacement. We studied about the structural properties of the plotted scaffold compared to conventional fabrication, such as salt leaching in a previous study [22]. We found that the plotted scaffold had more open and interconnected pore structures to induce cell ingrowth within the scaffold than a salt leached scaffold.…”
Section: Biochemical Analyses Of Scaffoldsmentioning
confidence: 98%
“…This study investigated the structural properties of hydroxyapatite scaffold for bone substitute replacement. We studied about the structural properties of the plotted scaffold compared to conventional fabrication, such as salt leaching in a previous study [22]. We found that the plotted scaffold had more open and interconnected pore structures to induce cell ingrowth within the scaffold than a salt leached scaffold.…”
Section: Biochemical Analyses Of Scaffoldsmentioning
confidence: 98%
“…In this study, the in vitro and in vivo characteristics of SLUP, conventional salt‐leaching and 3D‐plotted scaffolds were characterized. The 3D‐plotted scaffold, which is a SFF scaffold, has excellent biological behavior compared with the salt‐leaching scaffold due to its increased pore interconnectivity because of its well‐defined geometry . Moreover, the 3D‐plotted scaffold was fabricated with a 500‐μm strand size and 1000‐μm distances between strands.…”
Section: Discussionmentioning
confidence: 99%
“…6, 8, 10(b) and 6, 8, 10(c)). The SLUP scaffold groups were compared with recently reported studies . Lee et al, Park et al, and Sun et al showed that even if the porosity of salt‐leaching scaffolds were higher than those of 3D‐plotted scaffolds, cell ingrowth rates on the salt‐leaching scaffolds were lower than those on the 3D‐plotted scaffolds due to the poorer pore interconnectivity of the salt‐leaching scaffold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 8weeks of incubation it was observed that chondrocytes started filling up the interconnected pores and were fully spread on the 3D plotted scaffold surface. It was concluded that 3D plotted scaffold supports the speedy tissue formation with cell attachment in short time (Hee et al, 2010). Demonstration of different cell sources that are currently used in bone tissue regeneration is shown on Table 2.…”
Section: Journal Of Materials Science Researchmentioning
confidence: 96%